Comparison of DNA profiling between fishes and pork meat using polymerase chain reaction-restriction fragment length polymorphisms (PCR-RFLP) analysis - Safiyyah Shahimi,; Sahilah Abd. Mutalib,; Wan Sakeenah Wan Nazri,; Aminah Abdullah,; Norrakiah Abdullah Sani, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Genomic DNA of 13 fish (n=13) species consist of four freshwater which were catfish (Clarias gariepinus), shark catfish (Pangasius larnaudii), tilapia (Oreochromis mossambicus), perch (Lates calcarifer) and nine marine species which were black pomfret (Parastromateus niger), anchovy (Stolephorus commersonii), mabong (Rastrelliger kanagurta), red snapper (Lutjanus erythropterus), herring (Chirocentrus dorab), ray fish (Himantura gerrardii), sardine (Decapterus macrosoma), mackerel (Euthynnus affinis) and tuna (Thunnus tuna) were differentiated using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Seven endonucleases of AluI, BsaJI, HaeIII, HindIII, HinfI, MboI and MboII were examined for the ability to digest cyt b amplicon from each species. Genomic DNA of pork (Sus scrofa domestica) were differentiated from fishes by comparing the digestion patterns produced by similar amplified region and enzymes used. In the present study, it was demonstrated that fishes and pork DNA genome were successfully differentiated using all endonucleases except for HindIII. Thus, PCR-RFLP analysis was found useful for future pork DNA detection in fish products.